Direct self-focusing synthesis of monodisperse [Au8(PPh3)7]2+ nanoclusters. Issue 36 (6th September 2017) - Huang, Ting; Huang, Li; Jiang, Yong; Hu, Fengchun; Sun, Zhihu; Pan, Guoqiang; Wei, Shiqiang
Abstract : Direct synthesis of atomically monodisperse Au8 nanoclusters via the self-focusing process during NaBH4 reduction of Au(PPh3 )2 Cl. Abstract : Direct and scalable synthesis of monodisperse gold nanoclusters is highly desired but remains a great challenge due to the complexity of chemical reactions. In this regard, a suitable precursor is important as it can simplify the synthesis processes and offer controllability in tuning the product. In this study, we found that Au(PPh3 )2 Cl could be used as an effective precursor for the direct synthesis of atomically monodisperse [Au8 (PPh3 )7 ] 2+ nanoclusters without the need of tedious post-synthetic purification steps. The Au(PPh3 )2 Cl precursor could be directly reduced by NaBH4 (0.25 molar equivalent) in a dichloromethane solution; this produced Au8 clusters with a 35% reaction yield. Time-dependent mass spectrometry and in situ UV-vis absorption spectroscopy reveal that the synthesis process is initiated by the rapid formation of the Au6 –Au8 mixture, followed by a slow spontaneous self-focusing process that converges the mixture into atomically monodisperse Au8 . The success of this direct synthesis has been hypothesized to arise from the relatively stronger Au(i )⋯Au(i ) aurophilic attraction between Au(i )-PPh3 complexes that facilitates the aggregation of Au(i )-PPh3 on Au(0) cores.